Molecular mechanisms of endothelial dysfunction in Kawasaki-disease-associated vasculitis - Qiu, Yu; Zhang, Yulin; Li, Yifei; Hua, Yimin; Zhang, Yue (Frontiers in Cardiovascular Medicine, 2022)
Kawasaki disease (KD) is an acute, inflammation mediated vasculitis, mainly affecting in children under 5, which is consider as the most common coronary artery disease in children. The injuries of coronary arteries would result in dilation or thrombus formation, bringing great threaten to patients. Endothelium, located in the inner surface of coronary artery, serves as the interface between the circulating inflammatory cells and vascular media or adventitia, which is the first target of inflammatory attacks during early stage of KD. A series of studies have determined vascular endothelial cells damages and dysfunction in KD patients. However, current therapeutic strategy is still challenging. So that it is critical to underline the mechanisms of endothelium injuries. In this review, the role of endothelial cells in the pathogenesis of KD and the therapeutic methods for endothelial cells were systematically described.